A simple physical-activity-based model for managing children's activities against exposure to air pollutants. (1st February 2021) - Meng, Huicui; Zhang, Xiaoyu; Xiao, Jinqiu; Zhang, Yilan; Lin, Weiwei; Li, Zijian
Abstract: Air pollution has been a major health concern worldwide, such that there is an urgent need for exposure assessments of human exposure to air pollutants. As children are more active and may experience more exposure events than adults, it is more challenging to conduct exposure assessments for children. To obtain a general understanding of the impact that children's activity, associated with their respiratory rate (IR), has on estimated exposure risks, we adopted a simple model to narrow down children's exposure behaviors to four categories, which integrated children's regular schedules and the indoor–outdoor ratio ( r I / O ) of air pollutants. Although outdoor play only occupies approximately 8.6% of the total weekly time, the results indicate that, in general, outdoor play contributes to over 50% of the total exposure to air pollutants when r I / O is less than 0.1, which is due to children's relatively large IR during high-intensity activities. When air pollutants mainly originate from indoor sources (i.e., r I / O = 3.0 ), indoor sitting (28%) and sleeping (36%) account for the major portion of the total exposure due to the longer exposure duration while outdoor events, including playing, walking, and sitting, account for 15% of the total exposure. In addition, we applied a ratio function ( R M / C ) to compare our simple model to a common basic model, revealing that our simulated results are consistent with the basic model, i.e., 0.94 ≤ R M / C ≤ 1.12, if the r I / O of air pollutants falls in the range between 0.5 and 1.5. The sensitivity analysis indicates that indoor or outdoor play has a larger impact on the output results than other activity-related variables because of the correspondingly largest IR. We also incorporated weather factors to adjust children's activity schedules for winter and non-winter days showing the change in the contributions of children's activities to total exposure. For example, the contribution differential of outdoor play to the total exposure between winter and non-winter days is 8% for air pollutants with an r I / O value of 0.1. Although other factors, such as the activity intensity level and concentration of air pollutant in the microenvironment, must be refined in future studies, our simple model can be applied as a convenient approach to arrange children's activity schedules against possible air pollutant exposure. Highlights: A simple model is developed to manage children activities against air pollutants. Adopted simple model to narrow down children's exposure behaviors to four categories. Our results are consistent with the basic model when 0.5 ≤ r I / O ≤ 1.5. Outdoor play contributes to >50% of total exposure to air pollutants when r I / O < 0.1. Convenient approach for children's activity schedules against air pollutant exposure.